Pemasaran Pendidikan dalam Meningkatkan Kuantitas Peserta Didik di Raudhatul Athfal Nurul Jannah Kota Tangerang - Falahiyah Falahiyah; E. Syarifudin; Hanafi Hanafi (Departement of Mathematics Education, 2023)
Educational marketing is currently important for the survival of educational institutions. Educational institutions that are superior and in demand by many consumers are required to carry out active educational marketing, without marketing, school education will be unable to compete. This study describes the principal's educational marketing strategy in increasing the quantity of students. This research was conducted at RA Nurul Jannah, Neglasari District, Tangerang City. The method used in this research is qualitative through a case study approach. Data collection techniques in this study by observation, interviews and documentation. The results of the study reveal that there are six educational marketing strategies in increasing the quantity of students: product strategy, price, location, promotion, human resources, and infrastructure.